TCM body constitution study of diabetes and diabetes-related complications - Thein, Mwei Aung (Nanyang Technological University, 2022)
Background. Type 2 Diabetes Mellitus (T2DM) is a growing health problem worldwide. Individuals with T2DM are prone to both microvascular and macrovascular complications. Objective. To identify the Traditional Chinese Medicine (TCM) body constitution of T2DM and diabetes-related complications as well as the diabetic patient characteristics in Singapore. Methods. T2DM patients were recruited from Singapore Thong Chai Medical Institution (STCMI), all were interviewed using three Yin and three Yang body constitution questionnaire to assess body constitution. Diabetes complications as well as patient characteristics, including lifestyle, medical history and diabetes duration were recorded. Chi-squared tests were carried out using R V4.2.1. Results. There is a statistical significance between diabetes duration and complications. Body constitutions were also significantly associated with diabetes duration, with majority of them having Taiyin constitution diagnosed with >20 years of diabetes. After grouping the body constitution into Biao-Li pairs, Biao-Li constitution pairs were significantly associated with chronic kidney disease (CKD), microvascular complications of which most patients were in the Yangming-Taiyin constitution pair (P=0.03; P=0.02). Conclusion. The high proportion of Taiyin constitution among T2DM patients in Singapore could be due to dietary habits and Singapore’s climate and the results can be used for future health management of diabetes.